A revision of the genus Menonvillea (Cremolobeae, Brassicaceae) - Salariato, Diego Leonel; Zuloaga, Fernando Omar; Al-Shehbaz, Ihsan Ali (Phytotaxa, 2014)
Following the most recent phylogenetic analyses of Menonvillea, an updated taxonomic revision of the genus based on molecular and morphological data is presented here. Menonvillea currently includes 24 species distributed in Argentina and Chile. Three new sections, sects. Cuneata, Menonvillea, and Scapigera, are proposed. One subspecies is raised to the specific rank, and the new combination M. marticorenae is proposed. Descriptions, keys to all taxa, updated geographical distributions, maps, and illustrations are provided. Lectotypes for M. filifolia, M. minima, M. purpurea, and M. flexuosa f. tomentosa are designated.